"19 kids found in filth": how the Chicago Keystone Kids' case became emblematic of deviant motherhood and the crack cocaine crisis, 1985-2004. Issue 1 (2nd January 2022) - McCoy, Meghan
ABSTRACT: "Does society have the right to force pregnant drug addicts to abort their fetuses?" This was the question that Professor George Schendler from Southern Illinois University at Carbondale posed in his 1991 journal article. Schendler was not the only person to suggest criminalizing the behavior of pregnant people to prevent what were colloquially known as "crack babies." This article analyzes how discursive narratives of an immediate and long-term crisis, framed through the diseased body of an innocent yet simultaneously dangerous infant, erroneously predicted the onslaught of dependent Black and Brown children who would supposedly cripple American society. By focusing on the infamous 1994 "Keystone Kids" case in Chicago, IL, I argue that the steps taken to eliminate "crack babies" instead criminalized Black and Brown women's pregnancies and separated children from their parents.